2022
DOI: 10.1002/ep.14015
|View full text |Cite
|
Sign up to set email alerts
|

Decolorization of soybean oil by acid‐activated Ca‐Bentonite (EL Gnater, Central Tunisia)

Abstract: In the central Atlas of Tunisia, numerous outcrops of the upper Eocene provide smectitic clays. A representative sample (A) which was collected from the El Gnater region round El Ala underwent mineralogical and physicochemical analyses (granulometry, DRX, BET, FT-IR, etc.). This clay showing percentage of the order of 80% in smectite were activated with hydrochloric acid to improve its physicochemical properties, and consequently to increase their decolorization power for soybean oils. The best results were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
0
0
Order By: Relevance
“…The first adsorption stage was short in the first 10 min, followed by a slow process until equilibrium was attained after 40 min of reaction, which indicated that the maximum sorption of β-carotene occurred after 40 min of decolorization, which was in line with previous reports [35]. In the first stage, mainly β-carotene molecules react with the surface of activated clay; specifically, β-carotene is fixed to the clay surface by forming hydrogen bonds with Bronsted sites in the activated clay or by forming coordination bonds with Lewis sites [36]. In addition, the protonated AlOH 2 + structure can serve as an effective binding site for β-carotene in vegetable oil [37].…”
Section: Notesupporting
confidence: 90%
“…The first adsorption stage was short in the first 10 min, followed by a slow process until equilibrium was attained after 40 min of reaction, which indicated that the maximum sorption of β-carotene occurred after 40 min of decolorization, which was in line with previous reports [35]. In the first stage, mainly β-carotene molecules react with the surface of activated clay; specifically, β-carotene is fixed to the clay surface by forming hydrogen bonds with Bronsted sites in the activated clay or by forming coordination bonds with Lewis sites [36]. In addition, the protonated AlOH 2 + structure can serve as an effective binding site for β-carotene in vegetable oil [37].…”
Section: Notesupporting
confidence: 90%
“…Oil refining usually consists of degumming, deacidification, decolorization and deodorization steps, of which decolorization is one of the important processes in edible oil refining. Some studies have reported that solid adsorbents (e.g., clay and activated carbon) used in the decolorization process can bind to small molecules (e.g., pigments) in oils via physical adsorption [16,17]. Recently, it has been shown that decolorization is a key process to reduce some harmful compounds (e.g., BaP) [18][19][20].…”
Section: Introductionmentioning
confidence: 99%